2010
DOI: 10.1093/molehr/gaq065
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of Mad2 and Bub1 proteins is associated with spontaneous miscarriages

Abstract: During early development of the human embryo, chromosomal imbalance and instability may cause spontaneous miscarriages. In this study, we observe aberrant chromosome numbers in nearly half of spontaneous miscarriage embryo samples, most of which show abnormalities in karotype. We also detect significantly reduced expression of two important mitotic checkpoint proteins, Mad2 and Bub1. To further investigate the role of Bub1 and Mad2 in chromosome mis-segregation, in embryogenesis, and in errors leading to spont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…Gene ontology and pathway enrichment analysis found the 312 differentially expressed genes in the uncorrectable TS group were significantly enriched in biological processes like mitotic cell cycle, chromosome segregation and DNA packaging ( Figure 4b ), in cellular components like kinetochore, chromatin and spindle ( Figure 4c ), and in pathways like cell cycle, DNA replication and oocyte meiosis ( Figure 4d ). All these genes were expressed 2–8-folds higher in the uncorrectable TS group than in other groups, including key genes regulating spindle assembly checkpoint, such as BUB1, MAD2L1, AURKA, PLK1, CCNA2, CDK2, CENPE, CDC20 and BIRC5 [ 25–28 ], and those regulating the decatenation checkpoint, such as BRCA1, CCNB1, CDK1 and TOP2A [ 29 ], indicating a fundamentally different control of cell cycle checkpoints in the cell lines of this group. The gene expression levels were confirmed by qPCR ( Figure 4e ).…”
Section: Resultsmentioning
confidence: 99%
“…Gene ontology and pathway enrichment analysis found the 312 differentially expressed genes in the uncorrectable TS group were significantly enriched in biological processes like mitotic cell cycle, chromosome segregation and DNA packaging ( Figure 4b ), in cellular components like kinetochore, chromatin and spindle ( Figure 4c ), and in pathways like cell cycle, DNA replication and oocyte meiosis ( Figure 4d ). All these genes were expressed 2–8-folds higher in the uncorrectable TS group than in other groups, including key genes regulating spindle assembly checkpoint, such as BUB1, MAD2L1, AURKA, PLK1, CCNA2, CDK2, CENPE, CDC20 and BIRC5 [ 25–28 ], and those regulating the decatenation checkpoint, such as BRCA1, CCNB1, CDK1 and TOP2A [ 29 ], indicating a fundamentally different control of cell cycle checkpoints in the cell lines of this group. The gene expression levels were confirmed by qPCR ( Figure 4e ).…”
Section: Resultsmentioning
confidence: 99%
“…The action of miR-450a-3p is at least in part through down-regulation of Bub1. We previously found that the decreased expression of Bub1 proteins is associated with spontaneous miscarriages [13]. It is known that the impairment of the mitotic spindle checkpoint may play a major role in the cancer formation [31], [32].…”
Section: Discussionmentioning
confidence: 98%
“…Wells et al reported that the Bub1 expression is low in 2-cell embryos, but is significantly up-regulated in hatched blastocysts, indicating that the low level of Bub1 may be important for maintaining the stem cell properties prior to embryo implantation [12]. We previously found that the knockdown of Bub1 led to abnormal chromosomes in embryonic cells, and that the expression of Bub1 was significantly reduced and the numbers of spontaneous abortion embryo samples with aberrant numerical chromosome were increased [13]. However, it is unclear how Bub1 expression is regulated in this process.…”
Section: Introductionmentioning
confidence: 88%
“…The downregulation of the key component of the spindle checkpoint BubR1 causes an increase in polyploidy in murine embryonic fibroblast cells and enhanced megakaryopoiesis in bone marrow progenitor cells (Scannevin et al, 2004); BubR1 haploinsufficiency mice and RNA interference-mediated downregulation of this protein result in rapid tumor development (Dai et al, 2004). Downregulation of Mad1, in turn, causes SAC inactivation and aneuploidy (Kienitz et al, 2005), while reduced expression of Mad2 and Bub1 proteins is associated with spontaneous abortions (Shi et al, 2010). Loss of Bub1 below a critical threshold causes chromosome mis-segregation and can lead to spontaneous tumorigenesis (Basu et al, 1999;Jeganathan et al, 2007).…”
Section: Tumor Cells Frequently Show Altered Expression Levels Of Sacmentioning
confidence: 99%